(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Thrombophilia is defined as any alteration, either congenital or acquired, which promotes and/or facilitates the presentation of a thrombotic phenomenon. Drug treatment of this condition is to prevent (prophylaxis) other thrombotic event by anticoagulant therapy and hemostasis is affected, taking this great implication in the therapeutic approach in oral rehabilitation, leaning realize treatments with prosthetic structures on implants, teeth or tissue-borne. The aim of this case report is to present therapeutic alternatives in patients diagnosed with thrombophilia with protein C deficiency.